Pengaruh Struktur Modal, Kinerja Keuangan, dan Ukuran Perusahaan Terhadap Nilai Perusahaan Studi Empiris pada Perusahaan Index ISSI di Bursa Efek Indonesia - Novita Kurniawati; Adam Sugiarto (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to analyze the influence of capital structure, financial performance, and firm size on firm value in State-Owned Enterprises (SOEs) listed in ISSI Index in the Indonesia Stock Exchange (IDX). Firm value is measured using the Price to Book Value (PBV) rasio, capital structure is proxied by the Debt to Equity Rasio (DER), financial performance by Return on Assets (ROA), and firm size by company’s total assets. This research employs a quantitive approach using secondary data collected from the annual finansial reports of SOEs consistently included in the ISSI index during the 2020-2024 period. Data analysis was done using multiple linear regression with statistical software, E-Views. The result show that partially, capital structure has a positive effect on firm value, financial performance has no effect on firm value. effect on firm value, likewise firm size has no effect on firm value. Simultaneusly, the tree independent variables affect firm value. These findings imply that managing improving capital structure are strategic factor in increasing the firm value of Sharia-based SOEs. Meanwhile, finansial performance and firm size does not always reflect higher value from the investor’s perspective.